Performance of rooftop rainwater harvesting system as a source of drinking water - Aryal, Mamata; Joshi, Prayon; Thakuri, Sudeep (International Journal of Environment, 2022)
Rainwater Harvesting Systems (RWHSs) are increasingly being used as an alternative or supplementary source of water to curb the water supply deficit in the Kathmandu valley. The harvested rainwater is primarily used for non-potable purposes like flushing toilets and irrigation, but the knowledge on the use of rainwater for potable purpose is remarkably sparse. This study assesses the suitability of rainwater in terms of quantity and quality in a public school that adopts Rooftop RWHS as the source of drinking water. In this study, we observed that the volume of rainwater being harvested is sufficient to address the current demand of drinking water, with a mean rainfall of 1664 mm on a catchment area of 372 m2. Storage capacity  needs to be expanded if the demand increases. Physico-chemical and microbial analyses of water samples (before and after a series of treatments) were carried out for the winter, monsoon, and post-monsoon seasons. The values of physico-chemical parameters of the water samples, in all the seasons, were well within both the National Drinking Water Quality Standards (NDWQS, 2005) and the World Health Organisation (WHO, 2017) guidelines for drinking water, while fecal coliforms were detected in the storage tank, but were absent in tap water after the treatments. Based on the findings, we suggest that the harvested rainwater could be used for drinking purposes if properly treated. RWHS use at the institutional level, like in schools, on the one hand, curbs the increasing demand for water in water-deficit locations like Kathmandu, and on the other, encourages the adoption of such sustainable technologies for the water supply.